Informe: efectos del cambio climático sobre la producción del sector agrícola de Bolivia - Javier Aliaga Lordeman; Tirza J. Aguilar Salas (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2009)
– Bolivia as many other countries in the world, it is looking for some mechanism that allows to fight against the adverse impacts produced by climate variability. There is consensus that more adaptation and mitigation measures if we want to reduce the adverse effects produced by the climate change - in addition the vulnerability to these phenomena depends also on other stress factors. The aim of our research seeks to evaluate the economic impact of climate change in the agricultural sector of Bolivia with and without mitigation measures. From one hand the work quantify the effect of climate change over the GDP - from the other hand it evaluates the relevance of mitigation measures destined to reduce the risk and vulnerability of climate change. There are many methodologies that evaluate the incidence of climate change, both from economic and technological perspective - the first one in well known as bottom-up schemes - the second one is named top-down schemes. For the purposes of our research we use top-down model, based on Computable General Equilibrium (CGE) techniques.
Keywords: 330; Climate Change; Agricultural Sector; General Equilibrium Model